Customer connections: A cross-cultural investigation of brand experience and brand love in the retail landscape - Ângela Leite; Anabela Rodrigues; Sílvia Lopes (Administrative Sciences, 2024)
Brand experience, brand love, and brand behavior outcomes hold significant importance in management research. Their relevance extends to shaping strategic decision-making, fostering a customer-centric approach, and providing insights into the competitive landscape. These concepts are pivotal in understanding the complex dynamics of consumer-brand relationships, enabling organizations to make informed decisions, prioritize customer satisfaction, and stay competitive in the market. The present study aims to authenticate and assess the consistency of the Brand Experience (BE) scale and Brand Love (BL) scale in relation to the LIDL brand, comparing Portugal and the Czech Republic. Additionally, it delves into the connections between Brand Experience, Brand Love, and Brand Behaviour Outcomes (BBO): Positive Word of Mouth (+WOM), Brand Loyalty (BLYT), (Re)purchase Intention (RI), Affective Commitment (AC), Active Engagement (AE), and Perceptions of Attitudes Towards a Brand (PATB). The results demonstrated that the measurement tools used to gauge the variables under scrutiny are dependable and valid. Achieving measurement invariance across countries, convergence, and discriminant validity further validated the study. Positive correlations were identified among all the variables explored. The conceptual model tested exhibited a good fit and remained consistent across both countries. These findings hold significant implications for both academics and practitioners in the field of brand management.
Keywords: 350; brand behaviour outcomes (BBO); brand experience (BE); brand love (BL); retail; scale validity